DIABETES SELF MANAGEMENT DAN FAKTOR YANG MEMPENGARUHINYA PADA USIA DEWASA PERTENGAHAN - Sucipto Dwitanta; Debie Dahlia (Jurnal Ilmu Keperawatan Medikal Bedah, 2020)
Diabetes mellitus is six main causes of death in the world. Diabetes mellitus that is not managed properly can run the risk of causing various long-term complications. Type 2 diabetes has a prevalence of 2 to 2.5 times more risk of heart disease accompanied by microvascular and macrovascular complications. Prevent various kinds of life-threatening complications in middle adulthood is to use the diabetes self management (DSM) approach. DSM desperately needs commitment to a very complex diabetes management regimen to achieve good glycemic control. This literature review aims to analyze factors affecting diabetes self management in type 2 diabetes in middle-age adult patients. The literature review used in this study uses journal related by searching in scientific-based databases, with keywords used middle-age adult - diabetes self-management - type 2 diabetes. Based on the literature results, several factors that can affect DSM in middle-aged adult patients include depression, self-efficacy, social support, and knowledge. Therefore, the importance of further research is to be able to see which factors are the most influential among the four factors, so that nurses can make plans to overcome these problems.